Peningkatan Hasil Belajar Multimedia Matematika Melalui Flipped Classroom Berbantuan Webblog - Mulyono, Dodik; Hidayati, Atika Nur (JOEAI (Journal of Education and Instruction), 2020)
The purpose of this research was to improve the results of learning multimedia mathematics using a flipped clasroom-assisted approach to Webblog. The data collection method used is qualitative approach. Determination of subjects and objects in this study was done random sampling. The data sources used are the primary data source and the secondary data source. The results of pre-cycle research showed that the student learning results obtained were 4 students who completed or by 14.81%, then after being given action using flipped clasroom assisted Webblog experienced an increase in learning outcomes with students who completed in the first cycle by 25.92%, cycle II by 74.07% and cycle III by 92.59%. From the percentage results experienced success in the third cycle that meets the indicators of >75% complete success. In conclusion, there is an increase in student learning outcomes through the application of multimedia mathematics learning using flipped clasroom assisted Webblog to improve students' math learning outcomes. Keywords: Learning Results Mathematics, Multimedia, Learning flipped clasroom, Webblog